Graduate soft skills and employability in Malaysia: the view of employers from different manufacturing companies - Osman, Idris; Ibrahim, Alisa; Mohd, Idaya Husna; Mohd Hashim, Maryam Jameelah; Ahmad, Nursaadatun Nisak (UiTM Press, 2025)
Employers are increasingly concerned about graduates' shortcomings in soft skills, particularly in leadership, communication, and critical thinking. These deficiencies can negatively affect organisational performance and overall economic growth. This study examines the soft skills that are most valued by managerial personnel in manufacturing companies throughout the Klang Valley. It focuses on communication, critical thinking and problem-solving, leadership, and teamwork, as well as their influence on employability. A structured survey, adapted from the Malaysian Ministry of Higher Education, was administered to 173 managerial employees from various manufacturing firms. Data analysis was conducted using SPSS, which involved multiple regression analysis, reliability testing (Cronbach's alpha), and descriptive statistics. The findings revealed that critical thinking and problem-solving abilities are the most essential skills overall. However, teamwork showed the strongest relationship with employability, followed by communication, leadership, critical thinking, and problem-solving. These results emphasize the vital role that soft skills play in workforce readiness, supporting the employability skills model. To enhance managers’ competencies in teamwork and communication, the study recommends that organisations implement mentoring programs, leadership development initiatives, and targeted training. Higher education institutions should integrate experiential learning and structured soft skills development into their curricula to better align graduates' competencies with industry requirements. Additionally, policymakers are encouraged to promote soft skill development through targeted funding and sector-specific initiatives. Future research should investigate the long-term effects of individual soft skills across various industries and regions to more effectively anticipate the evolving demands of the labour market.